Analytical Verification and Studies on Degradation of Voglibose Nanocrystals Formulations using the Quantitative RP-HPLC Method - Aneja, Preeti; Guleria, Rajender; Dahiya, Dev Praksh; Swaminathan, Mohanraj (Indian Journal of Pharmaceutical Education and Research, 2026)
Introduction: The primary goal of the experiment was to validate a method for identifying Voglibose content in a newly developed Nano formulation specifically Nanocrystals. For estimating the content of voglibose in drug compounding, few analytical methods have been reported. This article presents a detailed validation of an RP-HPLC assay design for the quantification of Voglibose nanocrystals. Materials and Methods: In this study, a 250 x 4.6 mm, 5 μm RP-C18 column was employed for the separation. The mobile phase was laid a flow scale of 1 mL/min and expressed a combination of acetonitrile together with potassium dihydrogen phosphate buffer at pH 5.0 in the course of 40-60% (v/v) at 282 nm, the detection was completed. Over the analytical range of 50-170 µg/mL, a linear relationship (r2=0.99) was seen with the standard curve. Results: The method for quantifying Voglibose nanocrystals underwent successful validation, exhibiting its strength, accuracy, and sensitivity while fulfilling all necessary analytical reference solutions. The method manifested linearity across the examined concentration range and showed acceptable detection and quantification limits. Tests for reproducibility verified the method's consistency when used by different analysts and on various instruments. Conclusion: This is the first outcome for the validation of the voglibose nanocrystal formulation. This validated assay's effectiveness supports its use in the routine analysis of voglibose nanocrystals during research and development. It enables precise assessment of drug loading, release patterns, and stability studies. This study intends to help the development and regulatory compliance of voglibose formulations in clinical applications by addressing these crucial validation elements.
Keywords: Pharmaceutical; preparation; Reverse; Phase-High; Performance; Liquid; Chromatography; System suitability; Validation